DISPLAY LEVELS OF FAT, PROTEIN, AND LACTOSE OF COW'S MILK DUE TO ELEPHANT GRASS SUBSTITUTION WITH AMMONIATION RICE STRAW SUPPLIED TAPE TREE LEAVES - SUHARDI; PURWADI; SIGIT MURYANTO (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Research Objective is to evaluate what extent is XP, Living XP Fat, protein, and lactose levels Milk milk dairy Due Granting amber rice straw Supplemented Wood and Soyxyl Cassava leaves as a replacement of Elephant grass. Material used are 16 lactating dairy cattle on the 1st, 2nd, 3rd and 4th moons, elephant grass (RG), concentrate, ammonia rice straw (JPA), cassava leaves (DUK) and protein by pass brands This research was conducted using a randomized block design (RAK). Treatment applied: T0 = concentrate 65% + RG. 35%; T1 = Concentrate 65% + RG. 20% + JPA 5% + DUC 5% + Soyxyl 5%; T2 = Concentration 65% + RG. 15% + JPA 10% + DUC 5% + Soyxyl 5%; T3 = Concentration 65% + RG. 10% + JPA 15% + DUC 5% + Soyxyl 5%. Grouping is based on lactation Month 1, 2, 3 and 4 parameters Observed include: Feed consumption (BK), Fat content, protein and milk lactose level. The data obtained were processed statistically by using the variance analysis and if any differences would be continued with Duncan's test. The results showed that there was no real difference (P> 0.05) between the treatments T0, T1, T2 and T3. In addition, bypass proteins can be used to make up the elephant grass in lactase dairy cattle rations.